Menopausal age, related factors and climacteric symptoms in Libyan women - Taher, Y. A.; ben Emhemed, H. M.; Tawati, A. M. (Climacteric : the journal of the International Menopause Society, 2013)
ABSTRACT Objective Studies of the menopause have received much attention recently as fluctuating hormone levels are known to influence a woman's mood and well-being. The present study aimed to evaluate the onset of natural menopause in Libyan women together with the prevalence of postmenopause-related symptoms experienced. Method A cross-sectional survey was conducted in Tripoli city, from October 2008 to June 2009; 91 women were recruited from urban and rural areas. Data were collected using a structured questionnaire and included a number of lifestyle variables. Results The mean age of participants was 53 years, and the median age at menopause for postmenopausal women was 47 years. Out of 20 possible symptoms, the mean number of symptoms was 8.36. The most frequent symptoms were hot flushes and aching in muscles and joints (74.4%). Increasing level of education was positively associated with more symptoms, and increased tea or coffee consumption resulted in fewer symptoms. Of the total subjects, 8.1% reported no symptoms. In the four domains, 87.2% reported physical symptoms, 83.7% reported psychosocial symptoms, 76.6% reported vasomotor symptoms and 48.8% reported sexual symptoms. Our data showed that the most common disease associated with the frequency of menopausal symptoms was osteoarthritis, followed by hypertension, heart diseases and diabetes mellitus. Conclusion The age of menopause in Libyan women, as in other developing countries, is less than the median age reported for Western women. The menopausal women experienced various symptoms and morbidities as part of a normal life stage, and their quality of life was negatively affected by these symptoms.